The Primate Habituation Programme, Dzanga Sangha Protected Areas, Central African Republic: An overview - Terence Fuh Neba; Anna Feistner; Angelique Todd (Revue de Primatologie)
Dzanga Sangha Protected Areas (DSPA), including Dzanga-Ndoki National Park (DNNP), are located in SW Central African Republic (CAR) and are managed by the government and WWF. DSPA is CAR’s largest remaining nearly intact forest block and known for its outstanding biodiversity, including most of CAR's gorillas (G. g. gorilla). In 2012, DNNP, and its neighbouring NPs, were designated a World Heritage Site, the Sangha Tri-National complex (TNS) – classified as an exceptional priority area for western lowland gorilla and central chimpanzee (Pan t. troglodytes) conservation in the IUCN Regional Action Plan. The Primate Habituation Programme (PHP) was established in 1997 and plays a key role in DSPA’s conservation management strategy, generating significant revenue for the programme and tangible local community benefits. Now recognized as the most successful western lowland gorilla tourism and research programme, it has successfully habituated three groups, with another two undergoing habituation, and developed a controlled tourism programme. The habituated gorillas are regularly visited by tourists and are subjects of numerous scientific articles and film documentaries that have greatly contributed to our knowledge of this elusive species. Strong measures are in place to combat habitat loss and poaching in DSPA, but increased tourism, while providing income, can also negatively impact gorilla population health. Added to potential emerging diseases, human contact may increase stress and expose gorillas to human-borne pathogens, to which they may have little immunity. A PHP priority is to develop the programme into a model of sustainable best-practice with reduced risk of negative impacts from tourism/research. Current IUCN great ape tourism best practices (PHP is partly/fully compliant on ~90% of 156 criteria) include ongoing observational gorilla health monitoring, prohibiting visitors who are/have recently been ill and regular staff screening. However, disease risk, especially from asymptomatic pathogens, is a real threat and in order to monitor and mitigate these risks, the PHP set up a Wildlife Health Laboratory (WHL) in 2012. The main aim of this presentation is to give an overview of the PHP’s past, present and future activities (including habituation, research, tourism, and WHL), most of which continue despite the current political instability in CAR.